Salt sensitivity and myocardial fibrosis: unraveling the silent cardiovascular remodeling - Mutengo, Katongo Hope; Ngalamika, Owen; Kirabo, Annet; Masenga, Sepiso K. (Frontiers in Pharmacology, 2025)
Salt sensitivity is a well-recognized contributor to cardiovascular risk, traditionally linked to elevated blood pressure. However, emerging evidence suggests that high dietary sodium may also promote myocardial fibrosis through non-hemodynamic mechanisms, including the activation of redox-sensitive and profibrotic pathways. Despite growing mechanistic insights, the connection between salt sensitivity and myocardial fibrosis remains underexplored, particularly in human studies. This review synthesizes current experimental and translational evidence linking dietary salt intake to myocardial fibrosis, with a focus on molecular signaling cascades, tissue sodium compartmentalization, and the clinical implications of salt-sensitive physiology. We discuss the relevance of these mechanisms to the development of diastolic dysfunction and their potential contribution to heart failure with preserved ejection fraction (HFpEF). In addition, we highlight findings from animal models and the emerging application of sodium magnetic resonance imaging (23Na-MRI) as a novel imaging tool for visualizing myocardial sodium overload and its association with fibrotic remodeling. Finally, we explore future therapeutic strategies that extend beyond traditional antihypertensives, including mineralocorticoid receptor antagonists (MRAs), angiotensin receptor blockers (ARBs), sodium-glucose cotransport 2 (SGLT2) inhibitors, and sodium-modulating interventions. Together, these insights offer new opportunities for early detection and targeted treatment in salt-sensitive cardiovascular disease.